Anarchism, marxism, and nationalism in China: between conflict, cooperation and continuities - Müller-Saini, Gotelind (Routledge, 2023)
This chapter is part of the forthcoming volume Radical encounters in the colonial and postcolonial world, 1870-1940: anarchist, marxist, and nationalist struggles, edited by Steven Hirsch and Lucien van der Walt, Routledge
Keywords: China